1976
DOI: 10.1007/bf00041615
|View full text |Cite
|
Sign up to set email alerts
|

Variation in pollen viability in the onion (Allium cepa L.)

Abstract: INDEX WORDSAllium cepa, onion, pollen viability SUMMARY The pollen viability of onions in a glasshouse was recorded from May to October 1975, using the fluorescein test. The average viability was 60-95 % for most of this period but fell to less than 1% during the last two weeks of August. There was great variation in pollen viability between anthers within a flower and between flowers within a head. Attempts to induce pollen inviability by low temperature treatments at various stages of inflorescence developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…In some anthers, occasional production of fertile pollen in male‐sterile lines was observed which could be due to the high temperature effects on pollen production. Other authors (Meer and Bennekom , Ockendon and Gates) reported variation for pollen viability among flowers from same plant. Sen and Srivastava () were first to use male sterility from exotic sources, and other male‐sterile lines have been developed by other Indian researchers.…”
Section: Discussionmentioning
confidence: 95%
“…In some anthers, occasional production of fertile pollen in male‐sterile lines was observed which could be due to the high temperature effects on pollen production. Other authors (Meer and Bennekom , Ockendon and Gates) reported variation for pollen viability among flowers from same plant. Sen and Srivastava () were first to use male sterility from exotic sources, and other male‐sterile lines have been developed by other Indian researchers.…”
Section: Discussionmentioning
confidence: 95%
“…This variation among male-fertility-restored plants may be due to genetic background or environmental factors such as high temperatures at critical times of flower development (Barham and Munger, 1950;Meer and Bennekom, 1969). Ockendon and Gates (1976) reported variation for pollen viability among flowers from the same plant. In Beta vulgaris ssp.…”
Section: Resultsmentioning
confidence: 99%
“…Pollen viability in onion has been shown to vary, even down to anther level, though high viability is more commonly found than low (OCKENDON & GATES, 1976). Pollen viability differences might explain some of the results from the mixed pollinations, though the use of many anthers in a mixture would tend to even out viability differences within umbels.…”
Section: Discussionmentioning
confidence: 99%